Analysis of sewing quality of neckline, sleeves, and closures of women’s tops in selected stalls in Taytay tiangge - Villanueva, Bianca Margarita Ruta (College of Home Economics, University of the Philippines Diliman, 2023)
Several factors threaten the quality of garments sold in the tiangge in Taytay, tagged as the ‘garment capital’ of the Philippines (Allal et al., 1995). With this problem, the study aimed to analyze the sewing quality of neckline, sleeves, and closures of womenswear tops in selected stalls in the Taytay Tiangge. Specifically, it described the neckline, sleeves, and closures of selected womenswear tops manufactured in Taytay and sold by selected tiangge sellers, evaluated these using a Garment Analysis of Sewing Execution Checklist, and identified factors contributing to the quality of these garment parts. Data was collected from three participating stalls selected through purposive sampling. Three phases were conducted, mainly, through visual observation of store offerings, a quality evaluation of 12 garment samples selected based on the most produced women’s top in each stall using a checklist, and in-person interviews with the sellers. Garments were evaluated using a grading system based on the literature review wherein defects were categorized as either minor, major, or critical. Styles present in-store were primarily influenced by trends but limited by high costs and sewers’ unwillingness to perform difficult operations, resulting in the absence of closures in two of three stalls. Seven of 12 garment samples were rejected based on major defects found in the neckline, sleeves, and closures compromising garment functionality. Sewers’ carelessness and insufficient knowledge of machine operation, prioritization of price, lack of machine maintenance, and inadequate quality management were determined, through interviews with the sellers, as contributing factors to quality within the selected stalls. Skills training, a positive work environment, and the implementation of a comprehensive quality control system are recommended. Additionally, the researcher proposes further confirmatory studies on the quality of womenswear tops in Taytay Tiangge on a larger scale.